Non-hepatitis C virus crioglobulinemic vasculitis: a case series of nine patients - Cruz,Boris A. (2006)
INTRODUCTION: cryoglobulinemia vasculitis (CV) is a systemic vasculitis secondary to circulating immune complex deposition in small blood vessels. In the overwhelming majority of patients, it is associated to hepatitis C virus (HCV) infection, nevertheless it has been observed in a wide variety of diseases and in patients with no underling conditions - "essential cryoglobulinemia". OBJECTIVE: to report a series of patients with non-HCV CV. PATIENTS AND METHODS: a retrospective chart review of non-HCV CV patients was carried out by members of the Minas Gerais Vasculitis Study Group. Demographics, clinical, laboratory data, treatments and follow-up are reported. RESULTS: nine patients, two men and seven women, aged a 55.3 ± 17 years were studied. In three patients, CV was attributed to connective tissue disease and in one to a monoclonal gammopathy of undetermined significance (MGUS). Five patients presented essential cryoglobulinemia. Four patients presented bone marrow lymphoid infiltrates, but none developed overt lymphoma. All patients complained of myalgia/arthralgia. Eight patients (89%) presented cutaneous vasculitis; four patients (44%) had glomerulonephritis (GN) and six patients (67%) had neuropathy. Regarding treatment, six patients responded to steroids and immunosuppressive agents. Three patients were refractory to conventional therapy and therefore were treated with rituximab. After a follow-up of 19.3 ± 14 months, five patients (56%) were in partial remission and four patients (44%) were in complete remission. CONCLUSION: non-HCV cryoglobulinemia may present itself as a systemic vasculitis. It should not be understood as a simple inflammatory disease, since most patients present evidence of a lymphoproliferative disorders. Treatment should include steroids and immunosuppressive agents. Refractory patients may benefit themselves from rituximab.